A Ruth Suckow omnibus - Suckow, Ruth, 1892-1960 (Bur oak book., 1988)
This collection of ten short stories and one novella reintroduces a superb regional writer whose fiction, though firmly planted in the soil of the Midwest, stretches in significance to include all human drama. Despite her wide experience, Ruth Suckow became and remained a writer interested in small-town and small-city life. All her fiction contains deep and penetrating insights into the motivations of characters who are upheld by their dreams, memories of small-town childhoods, and the need to make sense of the contrast between past and present, idealism and practicality, con.